An Innovative Prone Position Using a Body-Shape Plaster Bed and Skull Traction for Posterior Cervical Spine Fracture Surgeries - Ding, Zhiyu; Ren, Yijun; Cao, Hongqing; Li, Yuezhan; Chen, Shijie; Miao, Jinglei; Li, Jinsong (Frontiers in Surgery, 2022)
Background A modified prone cervical spine surgical position using a body-shape plaster bed with skull traction (BSPST) was compared with the traditional prone surgical position with horseshoe headrests. Methods Forty-seven patients undergoing posterior cervical spine surgery for cervical spine fracture were retrospectively classified into two groups, BSPST group (n=24) and traditional group (n=23) and underwent posterior instrumented fusion with or without decompression. Multiple indicators were used to evaluate the advantages of the BSPST compared with the traditional position. Results All the operations went smoothly. The mean recovery rate was 56.30% in the BSPST group and 48.55% in the traditional group, with no significant difference. Intraoperative blood loss and total incidence of complications were significantly less in the BSPST group than in the traditional group. In addition, the BSPST position provided greater comfort level for the operators and allowed convenient intraoperative radiography. Conclusions This is the first study to describe a combined body-shape plaster bed and skull traction as a modified cervical spine prone surgical position that is simple, safe and stable, adjustable during surgery, reproducible and economical for posterior cervical spine fracture surgery and potentially other cervical and upper dorsal spine surgeries in the prone position. Additionally, this position provides surgeons a comfortable surgical field and can be easily achieved in most orthopedic operation rooms.